The role of changing geodynamics in the progressive contamination of Late Cretaceous to Late Miocene arc magmas in the southern Central Andes - Jones, R; Kirstein, L; Kasemann, S; Litvak, V; Poma, S; Alonso, R; Hinton, R (Elsevier, 2016)
The tectonic and geodynamic setting of the southern Central Andean convergent margin changed significantly between the Late Cretaceous and the Late Miocene, influencing magmatic activity and its geochemical composition. Here we investigate how these changes, which include changing slab-dip angle and convergence angles and rates, have influenced the contamination of the arc magmas with crustal material. Whole rock geochemical data for a suite of Late Cretaceous to Late Miocene arc rocks from the Pampean flat-slab segment (29–31 °S) of the southern Central Andes is presented alongside petrographic observations and high resolution age dating. In-situ U–Pb dating of magmatic zircon, combined with Ar–Ar dating of plagioclase, has led to an improved regional stratigraphy and provides an accurate temporal constraint for the geochemical data. A generally higher content of incompatible trace elements (e.g. Nb/Zr ratios from 0.019 to 0.083 and Nb/Yb from 1.5 to 16.4) is observed between the Late Cretaceous (~ 72 Ma), when the southern Central Andean margin is suggested to have been in extension, and the Miocene when the thickness of the continental crust increased and the angle of the subducting Nazca plate shallowed. Trace and rare earth element compositions obtained for the Late Cretaceous to Late Eocene arc magmatic rocks from the Principal Cordillera of Chile, combined with a lack of zircon inheritance, suggest limited assimilation of the overlying continental crust by arc magmas derived from the mantle wedge. A general increase in incompatible, fluid-mobile/immobile (e.g., Ba/Nb) and fluid-immobile/immobile (e.g., Nb/Zr) trace element ratios is attributed to the influence of the subducting slab on the melt source region and/or the influx of asthenospheric mantle. The Late Oligocene (~ 26 Ma) to Early Miocene (~ 17 Ma), and Late Miocene (~ 6 Ma) arc magmatic rocks present in the Frontal Cordillera show evidence for the bulk assimilation of the Permian–Triassic (P–T) basement, both on the basis of their trace and rare earth element compositions and the presence of P–T inherited zircon cores. Crustal reworking is also identified in the Argentinean Precordillera; Late Miocene (12–9 Ma) arc magmatic rocks display distinct trace element signatures (specifically low Th, U and REE concentrations) and contain inherited zircon cores with Proterozoic and P–T ages, suggesting the assimilation of both the P–T basement and a Grenville-aged basement. We conclude that changing geodynamics play an important role in determining the geochemical evolution of magmatic rocks at convergent margins and should be given due consideration when evaluating the petrogenesis of arc magmas.